Engagements with Students and Sustainable Development - Jain, Trilok Kumar (Journal of Advanced Research in English & Education, 2023)
This article explores the critical role of student engagement in fostering sustainable development. Student engagement encompasses a range of activities both inside and outside the classroom, contributing to the development of responsible individuals who play significant roles in society. The chapter delves into the definition of student engagement, identifying factors that constitute it, and discussing its various dimensions. It also examines the types of engagement, benefits for students and institutions, and the motivations driving student participation. The National Survey of Student Engagement (NSSE) and the Australasian Survey of Student Engagement (AUSSE) offer frameworks for understanding and assessing student engagement, with an emphasis on characteristics such as active learning, interactions with faculty, and rewarding educational experiences. The article emphasizes the positive correlation between student engagement and sustainability, highlighting its impact on overall student achievement and societal progress. The dimensions of engagement behavioral, emotional, and cognitive are explored, emphasizing the need for a holistic approach. The article discusses the transformative potential of student engagement in higher education, recognizing its pivotal role in shaping responsible citizens. It also addresses the diverse roles students can play in engagement, from passive observers to active decision-makers. The chapter concludes by examining the responsibility for student engagement, considering the roles of both students and institutions. It highlights the importance of collaborative efforts in creating effective student engagement strategies. The article touches upon specific methodologies, such as Action Learning Groups (ALGs) and tools for online learning, that enhance engagement. Finally, it discusses the impact of engagement on academic performance, emphasizing the evolving nature of student engagement in the contemporary higher education landscape.